Bioeficácia de fontes alternativas de metionina em relação à DL-metionina em frangos de corte (Cobb 500) - Sangali, Cleiton Pagliari (2012)
Aiming to assess the relative bioefficacy of DL-2-hydroxy-4-methylthio butanoic acid (DL-HMBA) and of poly-herbal ingredient (PHI) relative to DL-methionine (DLM) in broilers, two experiments were conducted. In the first experiment, 1100 Cobb 500 males and females broilers were fed either, from 1 to 21 days of age with a methionine-deficient basal diet, or the basal diet with three levels (0.170, 0.340, 0.511%) of DL-HMBA or three levels (0.111, 0.221, 0.332%) of DLM in equivalent amount of 65% of the levels of DL-HMBA or still, three levels (0.111, 0.221, 0.332%) of PHI, in equivalent amount the levels of DLM. In the second experiment, 900 Cobb 500 male broilers were fed either, from 22 to 42 days of age with a methionine-deficient basal diet, or the basal diet with three levels (0.143, 0.286 e 0.429%) of DL-HMBA or three levels (0.093, 0.186 e 0.279%) of DLM in equivalent amount of 65% of the levels of DL-HMBA or still, three levels (0.093, 0.186 e 0.279%) of PHI, in equivalent amount the levels of DLM. Simultaneous regression analysis was used to determine the bioefficacy based on weight gain and in feed conversion the of birds of experiments I and II, being that, in experiment II the bioefficacy values were also determined in function of the carcass characteristics of broilers fed with each methionine source. Performance was improved with supplementation of DL-HMBA or DLM in equivalent amount to 65% (DLM-65) of the levels of DL-HMBA, relative to those broilers fed the basal diet. However these responses were not so evident in birds supplemented with PHI. In the first experiment (stage of 1 to 21 days of age), simultaneous linear regression analysis revealed relative bioefficacy of DL-HMBA relative to DLM 39% and 44% for weight gain and feed conversion, on a product basis, respectively, being that, the performance data of birds supplemented with PHI not adjusted the simultaneously regression models, thereby, was not possible determine the bioefficacy of PHI in relation to the DLM. In the second experiment (stage of 22 to 42 days of age), simultaneous exponential regression analysis revealed bioefficacy relative of DL-HMBA and of PHI relative to DLM of 52% and 5% for weight gain and of 57% and 4% for feed conversion, on a product basis, respectively. To breast yield, the simultaneous linear regression analysis revealed relative bioefficacy of DL-HMBA in relation to DLM the 65% on a product basis. The results of this study indicate that the relative bioefficacy of DL-HMBA relative to DLM for broilers in stages of 1 to 21 and from 22 to 42 days old are respectively 42% and 58% on a product basis on average across all criteria tested